Non-Motor Symptoms in Patients Suffering from Motor Neuron Diseases - Günther, René; Richter, Nicole; Sauerbier, Anna; Chaudhuri, Kallol Ray; Martinez-Martin, Pablo; Storch, Alexander; Hermann, Andreas (Frontiers in Neurology, 2016)
Background The recently postulated “disease spreading hypothesis” has gained much attention, especially for Parkinson’s disease (PD). The various non-motor symptoms (NMS) in neurodegenerative diseases would be much better explained by this hypothesis than by the degeneration of disease-specific cell populations. Motor neuron disease (MND) is primarily known as a group of diseases with a selective loss of motor function. However, recent evidence suggests disease spreading into non-motor brain regions also in MND. The aim of this study was to comprehensively detect NMS in patients suffering from MND. Methods We used a self-rating questionnaire including 30 different items of gastrointestinal, autonomic, neuropsychiatric, and sleep complaints [NMS questionnaire (NMSQuest)], which is an established tool in PD patients. 90 MND patients were included and compared to 96 controls. Results In total, MND patients reported significantly higher NMS scores (median: 7 points) in comparison to controls (median: 4 points). Dribbling, impaired taste/smelling, impaired swallowing, weight loss, loss of interest, sad/blues, falling, and insomnia were significantly more prevalent in MND patients compared to controls. Interestingly, excessive sweating was more reported in the MND group. Correlation analysis revealed an increase of total NMS score with disease progression. Conclusion NMS in MND patients seemed to increase with disease progression, which would fit with the recently postulated “disease spreading hypothesis.” The total NMS score in the MND group significantly exceeded the score for the control group, but only 8 of the 30 single complaints of the NMSQuest were significantly more often reported by MND patients. Dribbling, impaired swallowing, weight loss, and falling could primarily be connected to motor neuron degeneration and declared as motor symptoms in MND.